Analisis Collaborative Governance Berbasis Pentahelix Dalam Pengembangan Pariwisata Pantai Mali Kabupaten Alor - Koby, Antonius (Jurnal Ilmiah Wahana Pendidikan, 2026)
Tourism is a strategic sector for driving regional economic growth and improving community welfare. However, tourism development requires a collaborative approach involving various stakeholders. This study aims to analyze the implementation of pentahelix-based collaborative governance in the development of tourism at Mali Beach, Alor Regency. The study employed a descriptive qualitative approach, with data collection techniques including in-depth interviews, field observations, and documentation. Informants included local government officials, local communities, tourism businesses, academics, and the media. The results indicate that the role of pentahelix stakeholders has not been optimally and equally implemented. Local government still dominates, while academic and media involvement is relatively low. Weak coordination, low participation in joint making decision, and the absence of a collaborative forum are major obstacles to the development of tourism at Mali Beach. This study recommends strengthening collaborative governance mechanisms through the establishment of an inclusive and sustainable pentahelix collaborative forum.